Calculation of activities in Ga-Cd and Cu-Pb binary systems - Manasijević Dragan; Živković Dragana; Živković Živan D. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Calculations of activities in Ga-Cd and Cu-Pb binary systems were done based on their known phase diagrams, using different calculation methods. First, activities of cadmium at 700 K and copper at 1263 K in Ca - Cd and Cu - Pb systems, respectively, were calculated by melting point depression method and Zhang-Chou method for binary systems with phase diagrams involving two liquid or solid coexisting phases. In order to obtain activity values in the entire composition range, these methods were applied in the definite parts of composition range in both investigating systems. The same procedure was done, using modified Rao- Belton method by Chou, who used Richardson assumption. Activities of the second component in both investigating systems were calculated by use of Gibbs-Duhem equation. All calculated results were compared with literature data and mutual comparison between applied methods was done.